Selected pollutants of the aquatic environment – challenges, health hazards, and remova - Karbowniczek, Martyna; Pajura, Rebeka; Kida, Małgorzata; Ziembowicz, Sabina; Mikuła, Karolina (Instal, 2024)
The current challenge for environmental protection is pollution from the group of emerging pollutants (ECs). Emerging contaminants are a group of highly toxic substances present in the environment at very low concentrations. These contaminants often enter aquatic ecosystems from various sources, such as pharmaceuticals, cosmetics, and industrial chemicals. Due to their bioaccumulative properties, ECs can move through the food chain, eventually reaching human bodies. Due to their bioaccumulative properties, ECs can move through the trophic chain, eventually reaching the human body. The aim of the article was to indicate the need for further research on the toxicity of these pollutants, their impact on the environment and human health, and to develop guidelines regulating their permissible concentrations. The importance of developing effective methods for removing ECs from various environmental components was also pointed out. Implementing these removal techniques, alongside regulations limiting the use of these substances, is essential to protect water quality and public health.
Keywords: pollutants; pollution removal; public health; environmental protection